Condition factors of two archerfish species from Johor Coastal Waters, Malaysia - Simon, K.D.; Mazlan, A.G.; Cob, Z.C. (Universiti Kebangsaan Malaysia, 2013)
Archerfishes Toxotes chatareus (Hamilton 1822) and Toxotes jaculatrix (Pallas 1767) inhabits mangrove estuaries, which are a critically important habitat as a spawning and nursery ground as well as the full life cycle of many fish species. In order to manage and conserve resilience fish species like the archerfish, we need to know some basic parameters about their biology and life history. Our research has focused on understanding the annual condition factors of these two species of archerfishes, as a complimentary to other several biological aspects of this two species that have been published. Our results indicated that, both species are in good conditions as the mean values of condition factors (Fulton condition factor K and Relative condition factor Kn) are greater than values of unity (K, Kn >1). The average K and Kn values of T. chatareus and T. jaculatrix were lowest in November and highest in September, indicates the spawning and recovery condition of the fishes. Condition factors measure overall fish population health that can be used by fisheries biologists and resource managers in proper management of fish resources in Malaysia waters.